Social Media Marketing Activities, Brand Awareness, and Brand Image of Commitment on Somethinc Product Tiktok Account - Kania Alayda Shafa; Anas Hidayat (Enrichment : Journal of Management, 2022)
Social media marketing activities tend to increase and become a trend in the business world. This study analyzes social media marketing activities, brand awareness, and image towards commitment to TikTok products Somethinc. Quantitative descriptive research design by including 305 respondents. Convenience sampling and questionnaires that passed the validity and reliability tests were used to collect the data. The study's findings revealed four variables that affect commitment and have a significant positive effect on some product TikTok accounts: social media marketing activities towards brand awareness (p = 0.000); social media marketing activities towards brand image (p= 0.000); social media marketing activities towards commitment (p= 0.000); and brand image to commitment (p= 0.024), but not brand awareness of commitment (p= 0.086). Hence, Somethinc, product managers need to increase brand awareness for product users.